Comparison of adiposity indices in relation to prehypertension by age and gender: A community‐based survey in Henan, China - Wang, Shuaibing; Peng, Rui; Liang, Shuying; Dong, Kaiyan; Nie, Wei; Yang, Qian; Ma, Nan; Zhang, Jianying; Wang, Kaijuan; Song, Chunhua (Clinical cardiology (Mahwah, N.J.), 2018)
Background To compare the efficiency of bioelectrical indices (visceral fat index [VFI], percentage body fat [PBF]) and anthropometric indices (body mass index, waist circumference, waist‐to‐height ratio, a body shape index ) in the relation to prehypertension (120‐139/80‐89 mm Hg) among the Chinese population. Methods Using stratified multistage random sampling method, a general population‐based sample of 11 175 adults in Henan province were selected from 2013 to 2015. The individuals were divided into three categories by blood pressure levels: normotension (<120 and 80 mm Hg), stage 1 prehypertension (120‐129/80‐84 mm Hg) and stage 2 prehypertension (130‐139/85‐89 mm Hg). Results VFI and PBF tended to increase with age in men and women. However, for each age‐specific group, men tended to have higher VFI than women (all P < 0.01) and women tended to have greater PBF (all P < 0.0001). The odds ratios (OR) and area under the receiver operating characteristic curves for prehypertension associated with adiposity indices declined with age. VFI and PBF showed higher standardized adjusted ORs for prehypertension in young (~40 years) men (VFI: 2.02‐3.05; PBF: 1.82‐2.80) and young women (VFI: 1.90‐2.58; PBF:1.70‐2.29). Moreover, based on Youden's index, VFI and PBF exhibited the superiority for identifying prehypertension in men (0.20‐0.32) and women (0.31‐0.39), respectively. Conclusion In summary, there was stronger association of VFI and PBF with prehypertension in men than in women, respectively, especially for young adults.